Performance analysis of porous radiant burn-ers for cooking applications - singh, Nageshwar; Chhabra, Saurabh; Sehgal, S.S.; Singh, Ishbir (International Journal of Engineering and Technology, 2017)
A new trend of utilizing the porous burner technology for the application of domestic cooking was observed because of its high efficiency and low emissions. This research work presents the experimental analysis of three types of porous burners having uniform diameter of 90 mm, 70 mm and divergent shape burner having the top diameter of 90 mm and bottom side diameter of 70 mm respectively. The fuel used for all the experimental trials was, Liquified Petroleum Gas (LPG). Porous burners consist of two zones i.e. preheating zone and combustion zone. The test piece preheating zone was filled with steel balls of diameter 6.5 mm and in combustion zone porous matrix of SiC foam of 10 ppi was used. Height of combustion zone was kept constant for all the three burners at 25 mm. Burner was operated at different equivalence ratio ranging from 0.10-0.60. The maximum efficiency of 79 % was observed for porous burner of diameter 90 mm at equivalence ratio (Φ) of 0.49 and 0.84 kW power.